The Existence of Law Number 27 Of 2022 Concerning Personal Data Protection in Protecting Citizens' Privacy Rights - Awaluddin (Indonesian Research Journal in Legal Studies, 2025)
This research aims to analyze and examine how Law Number 27 of 2022 plays a role as a legal instrument in ensuring the protection of citizens' privacy rights to personal data. In addition, this study also aims to assess the effectiveness of the norms and provisions regulated in the law, as well as evaluate institutional readiness to support its comprehensive implementation in the digital era. This research uses a normative legal method by examining laws and regulations and legal documents related to Law Number 27 of 2022 to examine the protection of citizens' privacy rights. The results of this study show that Law Number 27 of 2022 has been present as a special regulation that provides a clear and comprehensive legal basis in ensuring the protection of privacy rights for citizens' personal data. This law contains data protection principles in accordance with international standards, as well as regulates the rights of data subjects, the obligations of data controllers, and sanctions for violations. However, the effectiveness of the implementation of this law still faces structural obstacles, especially the lack of the formation of an independent supervisory institution which is an important element in carrying out the function of supervision and law enforcement optimally. It is recommended that the government immediately establish an independent supervisory institution and improve people's digital literacy to support the effectiveness of protecting privacy rights under the Personal Data Protection Law.